PERANCANGAN SISTEM INFORMASI PENYEWAAN LAPANGAN FUTSAL BERBASIS WEB MOBILE - Rudi Khairizal; Teguh Khristianto; Isworo Nugroho (Elkom : Jurnal Elektronika dan Komputer, 2021)
ABSTRACT A web-based futsal field reservation system was developed to help facilitate the process of booking or leasing a futsal field. The system uses PHP and HTML programming languages by using MySQL as data storage. The purpose of designing this system is to make it easier for users to rent futsal fields. With the futsal field reservation system is expected to facilitate in data processing, scheduling and registration of members or customers. In the end, this system is expected to help the company's performance, and can also facilitate customers in the ordering process.